2019
DOI: 10.1002/14651858.cd012305.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial agents for preventing urinary tract infections in adults undergoing cystoscopy

Abstract: BackgroundCystoscopy is commonly performed for diagnostic purposes to inspect the interior lining of the bladder. One disadvantage of cystoscopy is the risk of symptomatic urinary tract infection (UTI) due to pre-existing colonization or by introduction of bacteria at the time of the procedure. However, the incidence of symptomatic UTI following cystoscopy is low. Currently, there is no consensus on whether antimicrobial agents should be used to prevent symptomatic UTI for cystoscopy. ObjectivesTo assess the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…However, the current guidelines for antibiotic prophylaxis for cystoscopy are based on studies of mostly male patients when it is known that women are far more likely to develop UTIs than men 5 . Zeng et al 2 performed a systematic review investigating antibiotic prophylaxis for the prevention of UTI after cystoscopy. The review included 20 randomized controlled trials and 2 quasi-randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the current guidelines for antibiotic prophylaxis for cystoscopy are based on studies of mostly male patients when it is known that women are far more likely to develop UTIs than men 5 . Zeng et al 2 performed a systematic review investigating antibiotic prophylaxis for the prevention of UTI after cystoscopy. The review included 20 randomized controlled trials and 2 quasi-randomized controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…Urodynamic studies (UDS) and cystoscopy are frequently performed in the evaluation and treatment of female lower urinary tract dysfunction within a urogynecology practice. Urinary tract infection (UTI) is the most common complication after UDS and a known complication of cystoscopy 1,2 . A recent survey of the American Urogynecologic Society membership demonstrated that in the setting of UDS, 33% of respondents prescribed antibiotic prophylaxis to high risk patients, 14% prescribed antibiotic prophylaxis to all patients, whereas the remaining half never prescribed antibiotic prophylaxis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a Cochrane intervention review was published. 8 The paper included 20 RCTs and two quasi-RCTs with 7711 participants with the conclusions that antibiotics given for UTI prevention before cystoscopy may have little effect on the risk of developing serious infection, however, the quality of the evidence was rated low or very low. Similar studies conducted, to evaluate the potential benefit of AP before Transurethral Resection of the Bladder (TURB), concluded that antimicrobial prophylaxis could be safely avoided prior to TURB, in patients without pre-existing risk factors for UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of minimal knowledge on standard infection rates, and the difficulty in establishing practice-based rates due to patients seeking UTI treatments from different practitioners outside of their urogynecologist or urologist, these recommendations provide little guidance. Of note, a recent update of the Cochrane review on antibiotic prophylaxis for cystoscopy only indicated that antibiotic prophylaxis may reduce UTI [8].…”
Section: Introductionmentioning
confidence: 99%